IMPLIKASI KEPAILITAN TERHADAP PERUSAHAAN ASURANSI - Ahmad Djafri (Prodi Hukum S1 - Fakultas Hukum - Universitas Pamulang, 2018)
Abstract This research aims to show the implications of bankruptcy in insurance companies, both in the form of material implications for disadvantaged customers and in the form of national financial instability The existence of an insurance company is intended to minimize the risk posed to policyholders, but insolvency in insurance can occur. The research method used is normative juridical with reinforcement on empirical data, analyzed by qualitative normative methods The results of the study show first, insurance bankruptcy provisions are submitted by the Republic of Indonesia's finance ministry as a preventive measure for community loss of policyholders, secondly, the implications of bankruptcy on insurance companies can occur in the form of material losses to policyholders that must be replaced by insurance companies and the implications of loss of customer confidence insurance if the bankruptcy process is not completed properly.